VISUAL MEANING ANALYSIS OF ADVERTISEMENT “MARJAN 2022 (RAMADAN 1443 H)” - Lambok Hermanto Sihombing; Adithiya Wiradinatha Saputra (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2022)
This article discusses the analysis of visual meaning in Marjan 2022 advertisements. Every year, Marjan advertisements always come up with inspirational stories that come from stories of Indonesian people's habits. In 2022, Marjan is back in his advertisement with the theme Dewi Sri sang Pelindung, a figure who likes to help the community indiscriminately. This inspirational story certainly has an explicit meaning that not all levels of society understand what this advertisement means. Business people use advertisements with an explicit meaning to give a distinct impression to the potential target market. Therefore, this article discusses the meaning of the visual messages contained in the Marjan 2022 ad. The data used comes from the Marjan ad impressions broadcast on YouTube, since most people are very close to this platform. Researchers will use qualitative content analysis theory to obtain an accurate analysis to answer these problems. From the analysis results, the meaning contained in the Marjan 2022 advertisement describes the habits of the Indonesian people in all forms of activity that are different from other countries, namely the attitude of togetherness, helping each other, mutual sharing, generosity, and unyielding attitude.